1988
DOI: 10.1210/endo-123-3-1348
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Levels in the Peripheral Plasma and Hypothalamus of the Rat Vary in Parallel with Changes in the Pituitary-Adrenal Axis*

Abstract: Impressive evidence has emerged indicating that immunoassayable and bioassayable CRF, which is immunoneutralizable, is present not only in the hypothalamus but in many peripheral tissues as well. Using highly specific and sensitive RIAs and immunoaffinity chromatography to investigate whether this extrabrain CRF circulates in the rat, we found low but clearly measurable levels in peripheral plasma (mean, 11.4 +/- 0.8 pg/ml). Immunological findings were corroborated by fast protein liquid chromatography, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…In earlier studies, low basal plasma levels of CRH ranging from 5 to 13 pg/ml were detected in rats [20,32,33] as monitored using CRH antibodies, tracers and RIA conditions developed within investigators’ laboratories, leading to detection limits of approximately 5 pg/ml [20,23,33]. We previously reported that the use of the RAPID method for blood processing enables accurate measurement of circulating gut peptide concentrations, as assessed for acylated ghrelin, cholecystokinin-58, gastrin-releasing peptide and somatostatin-28, for instance [19], and extended here to endogenous CRH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, low basal plasma levels of CRH ranging from 5 to 13 pg/ml were detected in rats [20,32,33] as monitored using CRH antibodies, tracers and RIA conditions developed within investigators’ laboratories, leading to detection limits of approximately 5 pg/ml [20,23,33]. We previously reported that the use of the RAPID method for blood processing enables accurate measurement of circulating gut peptide concentrations, as assessed for acylated ghrelin, cholecystokinin-58, gastrin-releasing peptide and somatostatin-28, for instance [19], and extended here to endogenous CRH.…”
Section: Discussionmentioning
confidence: 99%
“…The RAPID method improves recovery and eliminates breakdown for most of the gut peptides tested [19]. Therefore, we first assessed whether the RAPID method would also improve the recovery of exogenous radiolabeled CRH added to blood in vitro compared to blood collected with EDTA only or followed by methanol extraction of the plasma as commonly performed in previous plasma assessments of CRH [14,20,21,22,23,24]. To extend our findings to circulating CRH, we next assessed basal plasma CRH levels determined by RIA kit when trunk blood from naïve rats was processed according to the RAPID method or collected with EDTA and plasma subjected or not to methanol extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma was separated, divided into two aliquots and stored at –30°C until assayed for corticosterone. Plasma levels of corticosterone were estimated, as a sensitive marker of the HPA axis activity [26], with a commercially available kit for rats ( 125 I-corticosterone radioimmunoassay; ICN Biomedicals, Costa Mesa, Calif., USA). The sensitivity of the assay was 0.40 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…However, this approach requires acute anesthesia and surgery, thus precluding studies of the axis in a basal state or of examining the effects of emotional stressors on function. Alternative approaches, including transnasal collection of hypophysial-portal blood from the awake sheep (8,9) and peripheral sampling in a variety of species (10)(11)(12)(13)(14)(15)(16)(17) have been attempted. In the present study, we have critically evaluated the validity of peripheral irCRF-41 measurements as an index of hypothalamic secretory activity by comparing peripheral and hypophysial-portal plasma irCRF-41 concentrations under a variety of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative inaccessibility of this specialized vascular link in species other than the sheep (8,9) prevents direct determination of irCRF-41 secretory profiles in the circulation at this level in the unanesthetized, ambulatory animal. Several laboratories have reported the presence of irCRF-41 in human or rat peripheral plasma (10)(11)(12)(13)(14)(15)(16)(17). During pregnancy, peripheral irCRF-41 appears to be derived from the placenta (18)(19)(20).…”
mentioning
confidence: 99%